Percutaneous nephrolithotomy in the pediatric age group: a study from North Karnataka - Kagalkar, Suresh; Agarwal, Surendra Kumar (International Surgery Journal, 2019)
Background: Nephrolithiasis is major problem in India. It is more prevalent in northern states of India and Karnataka is not an exception to this. Percutaneous nephrolithotomy (PCNL) has been accepted globally as a safe procedure with great success rate with less complication, and it is safe, effective, and suitable for pediatric cases. The aims and objectives of the study were to evaluate the indication of PCNL in children, to identify the complication, prevention and treatment of complication and to evaluate the efficacy and safely, management of kidney stones in children. Methods: Study period Aug 2015 July 2018, total 56 cases of renal stones in pediatric age group admitted in our Hospital, a tertiary care centre. All the patients evaluated for complete urine analysis, urine culture and sensitivity, complete hemogram, renal parameter, X ray KUB (kidney, ureter, and bladder), ultrasound KUB etc. Results: Small-stone (<2 cm) seen in 21.4% and large stone 64.2%. Following complications were noted- Pelvic perforations (3.5%), fever (7.1%) and hematuria (7.1%). Conclusions: PCNL is safe and effective procedure for the managements of renal stones in children with acceptable morbidity.